Mangifera indica Fruit Extract Improves Memory Impairment, Cholinergic Dysfunction, and Oxidative Stress Damage in Animal Model of Mild Cognitive Impairment. (29th January 2014) - Wattanathorn, Jintanaporn; Muchimapura, Supaporn; Thukham-Mee, Wipawee; Ingkaninan, Kornkanok; Wittaya-Areekul, Sakchai
Abstract : To date, the effective preventive paradigm against mild cognitive impairment (MCI) is required. Therefore, we aimed to determine whether Mangifera indica fruit extract, a substance possessing antioxidant and cognitive enhancing effects, could improve memory impairment, cholinergic dysfunction, and oxidative stress damage in animal model of mild cognitive impairment. Male Wistar rats, weighing 180–200 g, were orally given the extract at doses of 12.5, 50, and 200 mg·kg −1 BW for 2 weeks before and 1 week after the bilateral injection of AF64A (icv). At the end of study, spatial memory, cholinergic neurons density, MDA level, and the activities of SOD, CAT, and GSH-Px enzymes in hippocampus were determined. The results showed that all doses of extract could improve memory together with the decreased MDA level and the increased SOD and GSH-Px enzymes activities. The increased cholinergic neurons density in CA1 and CA3 of hippocampus was also observed in rats treated with the extract at doses of 50 and 200 mg·kg −1 BW. Therefore, our results suggested that M. indica, the potential protective agent against MCI, increased cholinergic function and the decreased oxidative stress which in turn enhanced memory. However, further researches are essential to elucidate the possible active ingredients and detail mechanism.